Identifying Student Teachers' Inquiry-Related Questions in Biology Lessons - Matti Hiltunen; Sirpa Kärkkäinen; Tuula Keinonen (MDPI AG, 2021)
Prior research has shown that both teacher-led and recitation questions dominate in classrooms; teachers ask closed-ended questions more than open-ended questions. Even though classroom questioning has been studied in many previous studies there has been very limited research addressing the questioning of student teachers during inquiry-based biology lessons focusing on the inquiry stages: introduction, examination, and conclusion. In this study, a total of 21 lessons by 12 student teachers in primary and secondary schools were video- and audio-recorded. The recorded discussions were transcribed and the qualities of the questions were analyzed using content analysis, and the questions of student teachers were categorized into 10 different question categories. The findings revealed that primary school student teachers asked mainly for factual knowledge, concepts, and basic knowledge of species in all inquiry stages. Secondary school student teachers also asked mainly for concepts and basic knowledge of species. They also asked students to generate ideas and explain their answers, especially in the examination and conclusion stages. The present study indicates that student teachers' questioning needs to be developed more towards higher-order questioning such as analyzing, synthetizing, and evaluating to scaffold students in inquiries and develop future teachers' questioning skills in teacher education.